Chest Physiotherapy: Pengoptimalan Self Care Pada Lansia di Yayasan Panti Werdha Theodora - Rezkiyanti Mutmainna Abdullah; Septirahellis Nur Afifah; Putri Sri Maharani; Arimbi Arimbi; Irfan Yunus (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Physiotherapy on the lungs or commonly called chest physiotherapy is one of the physiotherapy treatments aimed at overcoming problems related to the respiratory tract. The method used in this research is quantitative research. The main focus of this research is the elderly at Theodora Nursing Home Foundation who experience problems with breathing. This research was conducted using an approach and initial assessment, interviews, training, mentoring and evaluation. The mentoring and training activities of the Chest Physiotherapy Technique for the elderly at the Theodora Nursing Home Foundation aim to provide training and assistance to the elderly on how to know the importance of breathing exercise techniques to overcome problems in the elderly who are prone to respiratory problems. This research is expected to be a guideline for the implementation of assistance and training by foundation managers and the elderly at the Theodora Panti Werdha Foundation as a form of self-care that can be carried out by the elderly.